2014
DOI: 10.2478/s11756-014-0454-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Melia azedarach extracts against Spodoptera exigua

Abstract: Melia azedarach is a plant species whose fruits posses nematicidal and insecticidal activity. In this study, we tested two M. azedarach extracts: a crude methanolic fruit extract (CRU) and its limonoids fraction (LIM) produced after partitioning with dichloromethane to check their insecticidal activity against beet armyworm Spodoptera exigua. Both extracts disturbed development of S. exigua. After exposure to CRU and LIM, hatching success was slightly lower, larvalpupal and pupal-imago moulting was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Such fine alterations can be used as useful biomarkers of stress and indicate that the population is endangered by a stressor, and reacts before lethal effects can be observed. However, there are few data concerning ultrastructural alterations of cells and tissues of insects exposed to xenobiotics (Bishnupada et al, ; Lopez‐Villegas et al, ; Ntalli et al, ). Microscopic observations, especially transmission electron microscopy, may be also crucial for those researchers, who are interested in explaining the mechanism of action of particular substances or extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Such fine alterations can be used as useful biomarkers of stress and indicate that the population is endangered by a stressor, and reacts before lethal effects can be observed. However, there are few data concerning ultrastructural alterations of cells and tissues of insects exposed to xenobiotics (Bishnupada et al, ; Lopez‐Villegas et al, ; Ntalli et al, ). Microscopic observations, especially transmission electron microscopy, may be also crucial for those researchers, who are interested in explaining the mechanism of action of particular substances or extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the M. azedarach extracts and their limonoids exhibit various biological activities against insects, their effects on the insect heart activity were examined only in very few studies. As recorded by Ntalli et al (2014), the application of methanolic fruit extract of M. azedarach and its limonoids onto the 5 th instar larvae of S. exigua showed no significant effects on the heart contraction frequency in larvae but the heartbeat frequency was remarkably decreased only in the 1-day old pupae. In this context, a comprehensive study was conducted by Marciniak et al (2010).…”
Section: Affected Heartbeat By Botanicalsmentioning
confidence: 94%
“…Freshly collected potato and tomato leaves were collected and prepared as previously described (Cataldi et al 2005, Adamski et al 2014). The obtained extracts were diluted in distilled water to obtain final concentrations of 1, 10, 100 or 1000 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…In the series of the previous reports we showed that Solanaceae plants produce substances which can be used in crop protection (Adamski et al 2014, Ventrella et al 2015. Although they may not cause acute lethality of pests, several sublethal effects were observed, for example decreased fertility, lower hatching success or various morphological malformations (Büyükgüzel et al 2013, Ntalli et al 2014). These effects decrease number of individuals of pests inhabiting agrocenoses.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation